ANTIDotE: anti-tick vaccines to prevent tick-borne diseases in Europe - Hein Sprong; Jos Trentelman; Ingar Seemann; Libor Grubhoffer; Ryan OM Rego; Ondřej Hajdušek; Petr Kopáček; Radek Šíma; Ard M Nijhof; Juan Anguita; Peter Winter; Bjorn Rotter; et al. (Parasites & Vectors, 2014)
Abstract Ixodes ricinus transmits bacterial, protozoal and viral pathogens, causing disease and forming an increasing health concern in Europe. ANTIDotE is an European Commission funded consortium of seven institutes, which aims to identify and characterize tick proteins involved in feeding and pathogen transmission. The knowledge gained will be used to develop and evaluate anti-tick vaccines that may prevent multiple human tick-borne diseases. Strategies encompassing anti-tick vaccines to prevent transmission of pathogens to humans, animals or wildlife will be developed with relevant stakeholders with the ultimate aim of reducing the incidence of tick-borne diseases in humans.